Nilai-Nilai Kemanusiaan dalam Statement of the Services of Sir Stamford Raffles - Aulya, Salwa; Wijaya, Daya Negri (Universitas Hamzanwadi, 2025)
This article explores humanist values in Thomas Stamford Raffles' work, The Statement of Service, which acts as his defense against the accusations during his time in the Indonesian Archipelago. It uses a descriptive qualitative method with in-depth text analysis. The findings show that Raffles promoted humanist principles in his colonial policies, such as abolishing slavery, respecting local culture, and improving education. These policies reflect the influence of secular humanism, which Raffles embraced through his affiliation with the Freemason organization. However, the study also highlights contradictions between Raffles' humanist ideals and the colonial practices of his era. The research suggests further study on the relevance of Raffles' ideas to colonialism and modern humanism.